Development of Pervious Concrete with Enhanced Skid Resistance using Waste Tires Particles - Anwar, Muhammad Rizwan; Ahmad, Naqash; Khitab, Anwar; Khan, Raja Bilal Nasar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Rubber tires are excessively increasing with the advancement in transportation technologies. It is difficult to dispose off the tires and as such they cause environmental threats to the on-land and aquatic lives. In this work crumb rubber is used as a fractional replacement of sand in concrete at 5%, 10% and 15% by mass. The aim is to produce a porous concrete with acceptable mechanical strength and high skid resistance. The workability and fresh density of the concrete decreased with the crumb rubber. Similar reduction in mechanical strength was also noticed, however, 5% replacement showed mechanical properties similar to those of the control units. The crumb rubber enhanced the porosity of the material. The study as a whole suggests that a lightweight concrete with enhanced porosity and skid resistance can be produced by recycling crumb rubber as a partial replacement of sand. The porous concrete with good skid resistance is a useful pavement material as it allows the infiltration of rainwater through it and thus has the capacity to reduce runoff during heavy rainfalls. It can additionally help reduce the accidents due to higher skid resistance in wet conditions.